Centipedegrass for Florida Lawns - J. B. Unruh; A. J. Lindsey; M. Schiavon (EDIS)
Centipedegrass is a commonly grown, low input turfgrass used in landscapes throughout the state of Florida. This factsheet provide science based information on the culture and management of centipedegrass including mowing, irrigation, pest control, and cultural practices.